(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes the dynamic allocation of the burden of proof in labor procedure as an instrument for the effectiveness of substantive equality. Its objective is to demonstrate that the flexibilization of the probative burden, provided for in Article 818 of the CLT and Article 373 of the CPC, is not merely a procedural technique, but an indispensable measure to overcome the structural inequality between employee and employer and to ensure the realization of fundamental rights. The methodology consisted of theoretical-dogmatic and bibliographic research, based on authors such as Miguel Reale, Alfonso López Quintás, Hegel, and Feliciano, in addition to labor and procedural legislation. The study articulated social reality, legal theory, and axiological hermeneutics to highlight that evidence must be interpreted in dialogue with constitutional values. The results showed that the dynamic theory is essential in cases of difficult proof, such as discrimination, harassment, and labor environmental violations. It concludes that the redistribution of the burden of proof is a methodological and axiological development that reaffirms the protective mission of Labor Law. Keywords: Dynamic allocation of the burden proof. Substantive equality. Labor procedure.